PEKERJA ANAK DI SURAKARTA MASA KOLONIAL: DARI PEKERJA KELUARGA MENJADI PEKERJA UPAH - Hayu Adi Darmarastri (SASDAYA: Gadjah Mada Journal of Humanities, 2017)
This article aims to explain about the alteration of the child labour which originally served as a family worker and later became a wage worker at the Surakarta’s during the colonial period. Children in Javanese rural community have been taught since an early age to help their parents, by doing house chores as well as work in the field. Those lessons transform child to be a family worker who helps their parent’s work without receiving any money. The position changed with the arrival of foreign capital who rented land in the Surakarta region to be used to grow cash crops that were sold in the world market, such as coffee, sugar cane and tobacco. Along with many plantations opened, more workers were needed. The limited number of existing workers is an entry point for women and children to work as wage workers in Surakarta’s plantations, one of which is the tobacco plantation.